THE CONFUSING TAXONOMY AND NOMENCLATURE OF SYZYGIUM CONFUSUM COMPLEX (MYRTACEAE) - Pudji Widodo; Jan Frits Veldkamp (REINWARDTIA, 2021)
WIDODO, P. & VELDKAMP, J. F. 2021. The confusing taxonomy and nomenclature of Syzygiun confusum complex (Myrtaceae). Reinwardtia 20(2): 43‒49. ― The taxonomic and nomenclatural confusions surrounding the Syzygium confusum complex are elucidated. For that purpose, type specimens are designated and circumscriptions are presented for each species. Typifications, newly characterized descriptions and illustrations are presented for Syzygium korthalsii Widodo, S. confusum (Blume) Bakh.f., S. blumei (Steudel) Merr. & L.M.Perry, S. insigne (Blume) Merr. & L.M.Perry. The new species Syzygium sipirokense Widodo & Veldkamp is described.